2020
DOI: 10.1097/mrr.0000000000000452
|View full text |Cite
|
Sign up to set email alerts
|

A new valid Walking Aid Scale better predicts distance walked by prosthesis users than Prosthetic Mobility Questionnaire 2.0 and Activities-Specific Balance Confidence Scale

Abstract: The availability of psychometrically-sound and parsimonious outcome measures is key for optimizing decision-making about prosthetic fitting and rehabilitation in lower limb prosthesis users. Despite the increasing clinical use of observational and self-reported scales for assessing mobility and balance, there is currently no scale that accounts for the use of assistive devices while walking under conditions of increasing difficulty. Therefore, the purpose of this study was to develop and validate a Walking Aid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 31 publications
3
4
0
Order By: Relevance
“…In summary, this Rasch study demonstrated the good measurement quality of the PMQ 2.0, in line with other studies performed using Italian, 8 Slovene, 9-11 and German 12 versions. It also confirmed acceptable psychometric properties of the PEQ-MS, 5,22 despite some weakness in its item selection.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In summary, this Rasch study demonstrated the good measurement quality of the PMQ 2.0, in line with other studies performed using Italian, 8 Slovene, 9-11 and German 12 versions. It also confirmed acceptable psychometric properties of the PEQ-MS, 5,22 despite some weakness in its item selection.…”
Section: Discussionsupporting
confidence: 90%
“…Nevertheless, our findings related to the psychometric characteristics of the investigated tools are in line with other studies using the same instruments, but performed in different contexts. 5,9,10,12 In summary, this Rasch study demonstrated the good measurement quality of the PMQ 2.0, in line with other studies performed using Italian, 8 Slovene, [9][10][11] and German 12 versions. It also confirmed acceptable psychometric properties of the PEQ-MS, 5,22 despite some weakness in its item selection.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Two validated PROMs for measuring mobility with the prosthesis in people with LLA are the Locomotor Capabilities Index (LCI-5) [10,11] and the Prosthetic Mobility Questionnaire (PMQ 2.0) [12–14], which are available also in German versions: the former already published [15], while the latter submitted for publication (Ranker et al ., 2021, unpublished material). They are both promising tools but, so far, no head-to-head comparison of them has been performed.…”
Section: Introductionmentioning
confidence: 99%